Hypovitaminosis D Causing Idiopathic Musculoskeletal Pain in Children - Karim, Rahida; Afridi, Jahanzeb Khan; Ullah, Hameed; Zaman, Muhammad Batoor; Amjad, Afnan; Naeem, Sobia; Amjad, Maha (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES To determine the frequency of hypovitaminosis D in children presenting with Idiopathic musculoskeletal pain IMSP). METHODOLOGY The cross-sectional research was carried out at Peshawar’s Hayatabad Medical Complex’s Department of Pediatrics. The study duration was 6 months. The study comprised 151 patients with non-specific musculoskeletal pain who were tested for vitamin D levels to diagnose hypovitaminosis. RESULTS The age range of the participants was 3 to 15 years with a male predominance of 72.8%. The sample’s average the weight was above the 25 percentile. Hypovitaminosis D was found in 23.2%. Decreased sun exposure was documented in 82.85% of cases with hypovitaminosis. Hypocalcemia, hypophosphatemia and increased alkaline phosphatase were documented in 71.4%, 11.4% and 42.8% participants respectively with hypovitaminosis. CONCLUSION Hypovitaminosis D Is one of the risk factors for non-specific musculoskeletal pain but the current study revealed only 23.2% of participants had hypovitaminosis and inadequate sun exposure was a major risk factor for hypovitaminosis.